Boundaries and justice : diverse ethical perspectives - Miller, David, 1946-; Hashmi, Sohail H., 1962- (Ethikon series in comparative ethics., 2001)
Despite the supreme political and economic significance of boundaries--and ongoing challenges to existing national boundaries--scant attention has been paid to their ethics. This volume explores how diverse ethical traditions understand the political and property rights reflected in territorial and jurisdictional boundaries. It is the first book to bring together thinkers from a range of traditions, both religious and secular, to discuss the ethics of boundaries. Each contributor represents a tradition's views on questions surrounding the use of boundaries to delimit property and political rights. What does it mean to own something? What resources should not be privately owned? What justifies the erection of political boundaries between one people and another? How ''hard'' should such boundaries be? What rights extend to minorities within a state? Should territorial boundaries coincide with social ones? Does national autonomy have an ethical basis, or is it an aspect of modern power politics? Should we aim for a more inclusive community than that afforded by modern nation-states? Cross-chapter dialogue and a substantive conclusion draw out similarities and differences among the traditions represented, traditions that include Christianity, classical liberalism, Confucianism, international law, Islam, Judaism, liberal egalitarianism, and natural law. In addition to the editors, the contributors are Nigel Biggar, Joseph Boyle, Joseph Chan, Russell Hardin, Will Kymlicka, Loren Lomasky, Robert McCorquodale, Richard B. Miller, David Novak, Sulayman Nyang, Michael Nylan, Raul C. Pangalangan, Daniel Philpott, Jeremy Rabkin, Hillel Steiner, M. Raquibuz Zaman, and Noam J. Zohar.